2007
DOI: 10.1002/dac.916
|View full text |Cite
|
Sign up to set email alerts
|

IPv6 delay and loss performance evolution

Abstract: SUMMARYAlthough packet delay and loss are two important parameters of the Internet performance, to the best of our knowledge, the evolution of large-scale IPv6 delay and loss performance has previously not been studied. In this paper, we analyze more than 600 end-to-end IPv6 paths between about 26 testboxes of RIPE Network Coordination Centre over two years, and compare the delay and loss performance over time with their IPv4 counterparts. We present and discuss the measurement methodologies and show that IPv6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Zhou et al [16] found that IPv6 paths have a higher delay and loss than their IPv4 counterparts, mainly due to its poor performance in IPv6-in-IPv4 tunnels. Nikkhah et al [17] and Dhamdhere et al [20] found that IPv6 delay is similar to IPv4 performance when the ASlevel paths are identical.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhou et al [16] found that IPv6 paths have a higher delay and loss than their IPv4 counterparts, mainly due to its poor performance in IPv6-in-IPv4 tunnels. Nikkhah et al [17] and Dhamdhere et al [20] found that IPv6 delay is similar to IPv4 performance when the ASlevel paths are identical.…”
Section: Related Workmentioning
confidence: 99%
“…Investigating the performance of IPv6 network is the basis of guaranteeing the network with a good performance. Therefore, many studies have been performed to analyze IPv6 network performance, as well as figure out the differences between IPv4 and IPv6 [13][14][15][16][17]. However, our understanding of IPv6 network cannot catch up with the speed of its development.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have focused on quantifying adoption across Autonomous Systems (ASes) [15], [39], among end-users [16], and in Operating Systems (OSes) [8], [21]. Performance issues in OSes have been explored in [34], [49], while investigations aimed at end-to-end performance have compared IPv4 and IPv6 using metrics such as path delay and packet loss [47], [50]. On the modeling front, many studies have sought to formulate the IPv6 adoption question in the context of an economic framework, in an attempt to capture the many interacting factors affecting it [14], [18], [35], [42].…”
Section: Related Workmentioning
confidence: 99%
“…For IPv6-IPv4-IPv6 tunnels the difference is a 60% with no ACLs and a 630% of increased delay with ACLs. Xiaoming Zhou et al performed delay measured as well in [15]. They compare the delay and packet loss between IPv6 and IPv4 analyzing over 600 end to end pats.…”
Section: Related Workmentioning
confidence: 99%